'I don't want to be distinguished by others': language ideologies and identity construction among North Korean refugees in South Korea. Issue 3 (3rd July 2022) - Park, Mi Yung
Abstract: This study explores how North Korean refugees in South Korea navigate different ideologies about language and construct their own language ideologies and identities while adjusting to and learning a new variety of Korean. Drawing on interviews with four North Korean refugees, the study finds that they have suffered from stigmatization because of their socially marked North Korean accents, leading them to internalize a hierarchical view of the two varieties of Korean and to strive to speak like South Koreans. The participants have at times strategically concealed their identities in order to pass as non-North Korean and protect themselves from discrimination. However, the participants have also positioned and repositioned themselves and their linguistic and cultural resources through imagining different possible futures. Challenging the inferior identities imposed on them by the mainstream society, they have constructed imagined identities as valuable assets for a future, reunified Korea. In doing so, they have used their bidialectal and bicultural skills to differentiate themselves from South Koreans and empower themselves. The findings of the study shed light on the complex interactions between language ideologies, language use, and identity construction, with implications for refugee language-support programs.